Awareness and Impact of International Normalized Ratio Monitoring in Ongoing Anticoagulation Therapy in Cardiac Patients - Pal, Mriganka; Bandari, Suresh; Gier, Scott; Sekar, Chandra (Indian Journal of Pharmacy Practice)
Objectives: The objectives of the current study is to determine the extent of awareness and the level of understanding about INR testing among patients undergoing oral anti-coagulation (OAT) therapy and to determine whether their INR values are within therapeutic range as measured by Coagucheck on-site INR. Results: For our study we interviewed 205 patients, and enrolled 90 patients that lasted for 6 months. Patient population recruited in the study comprised of 53 males and 37 females and INR was determined on-spot for these patients by CoaguChek. Majority of patients enrolled in this study were in the age group 20-59. Results indicate that more patients lacked awareness than aware of the importance of INR. Among 63 patients who were unaware about the significance of regular INR testing, 74.60% get their INR tested only if asked by a physician, 22.22% get their INR tested on a monthly basis and 3.17% get their INR checked every week. Whereas, among the 27 patients who were aware, 70.37% gets their INR tested on a weekly basis, 25.92% gets tested on a monthly basis and only 3.70% do it only if asked by a physician. Results also revealed that a greater proportion of the patients in the “lack of aware group” have INR values that are beyond the therapeutic range. Of the total of 7 Bleeding events reported by patients in this study, 6 were reported by patients who belonged to the “lack of aware group”. Conclusion: Our study clearly demonstrates that ignorance regarding the significance of INR is clearly associated with increased incidence of bleeding. Patient education in conjunction with on-site INR testing by the pharmacist will both save lives and improve therapeutic outcome.
Keywords: Warfarin; Anticoagulation; Monitoring; INR; On-site; Coagucheck. Indian hospital